Possible reasons for an increase in the proportion of genital ulcers due to herpes simplex virus from a cohort of female bar workers in Tanzania. Issue 2 (13th September 2006) - Riedner, Gabriele; Todd, Jim; Rusizoka, Mary; Mmbando, Donan; Maboko, Leonard; Lyamuya, Eligius; Hoffmann, Oliver; MacLean, I; Grosskurth, Heiner; Hayes, Richard
Abstract : Objectives: To determine trends in the prevalence and aetiological distribution of genital ulcer syndrome (GUS) in a cohort of female bar workers and to assess factors associated with these trends. Methods: An open cohort of 600 women at high risk of HIV and sexually transmitted infection (STI) was offered screening and treatment for STI at 3-month intervals. The prevalence of GUS and associated aetiological agents (Herpes simplex virus (HSV), Treponema pallidum and Haemophilus ducreyi ) were monitored over 27 months through clinical examination, dry lesion swabbing and multiplex polymerase chain reaction. The effects of HIV status and other factors on the prevalence trends of STI were assessed. Results: A total of 753 women were recruited into the cohort over 10 examination rounds. At recruitment, the seroprevalence was 67% for HIV and 89% for HSV type 2 (HSV-2). During follow-up, 57% of ulcers had unknown aetiology, 37% were due to genital herpes and 6% to bacterial aetiologies, which disappeared completely in later rounds. The absolute prevalence of genital herpes remained stable at around 2%. The proportion of GUS caused by HSV increased from 22% to 58%, whereas bacterial causes declined. These trends were observed in both HIV-negative and HIV-positive women. Conclusions: The changes observed in the frequency and proportional distribution of GUS aetiologies suggest that regular STI screening and treatment over an extended period can effectively reduce bacterial STI and should therefore be sustained. However, in populations with a high prevalence of HSV-2, there remains a considerable burden of genital herpes, which soon becomes the predominant cause of GUS. Given the observed associations between genital herpes and HIV transmission, high priority should be given to the evaluation of potential interventions to control HSV-2 either through a vaccine or through episodic or suppressive antiviral therapy and primary prevention.